Raging star - Young, Moira (London : Marion Llyod Books : Scholastic, 2014)
Saba leads a group of guerrillas against DeMalo and the Tonton, all while contemplating DeMalo's invitation to join him in building a New Eden.
Young Adult.
Young Adult
Keywords: Brothers and sisters -- Juvenile fiction; Guerrilla warfare -- Juvenile fiction; Orphans -- Juvenile fiction; Telepathy -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Fiction; Guerrilla warfare -- Fiction; Orphans -- Fiction; Telepathy -- Fiction; Twins -- Fiction; Guerrilla warfare -- Fiction; Orphans -- Fiction; Siblings -- Fiction; Telepathy -- Fiction; Twins -- Fiction